Indirubin attenuates sepsis by targeting the EGFR/SRC/PI3K and NF-κB/MAPK signaling pathways in macrophages - Li, Yancen; Wan, Chengyu; Li, Fan; Xin, Guang; Wang, Tao; Zhou, Qilong; Wen, Tingyu; Li, Shiyi; Chen, Xiaoting; Huang, Wen (Frontiers in Pharmacology, 2025)
BackgroundIsatidis Folium, a botanical drug widely used in traditional medicine, is known for its anti-inflammatory properties, including heat-clearing, detoxifying, and blood-cooling effects. Although its potential in sepsis treatment has been suggested, the bioactive metabolites and underlying mechanisms remain poorly understood.MethodsNetwork pharmacology and molecular docking were employed to identify the therapeutic effects and mechanisms of Indirubin, the major bioactive metabolite of Isatidis Folium, in sepsis treatment. In vivo, a cecal ligation and puncture (CLP)-induced mouse sepsis model was used to evaluate the protective effects of Indirubin through histopathological analysis, ELISA, and biochemical assays. In vitro, RAW264.7 cells were stimulated with LPS and treated with varying concentrations of Indirubin. The anti-inflammatory effects of Indirubin were assessed using ELISA, apoptosis assays, and Western blotting.ResultsNetwork pharmacology analysis identified Indirubin as the major bioactive metabolite of Isatidis Folium and EGFR and SRC as its key molecular targets. Experimental validation demonstrated that Indirubin significantly improved survival rates, alleviated tissue injury, and suppressed inflammatory responses in sepsis models. Mechanistically, Indirubin inhibited LPS-induced activation of the EGFR/SRC/PI3K and NF-κB/MAPK pathways in macrophages, significantly reducing cell death and inflammation in RAW264.7 cells.ConclusionIndirubin, the primary bioactive metabolite of Isatidis Folium, exerts protective effects against sepsis by targeting the EGFR/SRC/PI3K and NF-κB/MAPK signaling pathways in macrophages. These findings provide a mechanistic basis for the development of Indirubin as a multi-target therapeutic agent for sepsis treatment.